2023
DOI: 10.1109/access.2023.3268703
|View full text |Cite
|
Sign up to set email alerts
|

Cut-Out Scenario Generation With Reasonability Foreseeable Parameter Range From Real Highway Dataset for Autonomous Vehicle Assessment

Abstract: This work was funded by the Ministry of Economy, Trade and Industry of Japan through the SAKURA project (https://www.sakura-prj.go.jp/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Similar as in (Nakamura et al, 2022;Muslim et al, 2023), both approaches presented in this work construct a PDF which is used to estimate the range of the parameters of the reasonably foreseeable scenarios.…”
Section: Discussion Related To Reasonably Foreseeable Scenariosmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar as in (Nakamura et al, 2022;Muslim et al, 2023), both approaches presented in this work construct a PDF which is used to estimate the range of the parameters of the reasonably foreseeable scenarios.…”
Section: Discussion Related To Reasonably Foreseeable Scenariosmentioning
confidence: 99%
“…Our proposed methods differ from the method used in (Nakamura et al, 2022;Muslim et al, 2023) because fewer assumptions regarding the PDF estimation are made. In (Nakamura et al, 2022;Muslim et al, 2023), it is assumed that the scenario parameters are independent, that the parameters are distributed according to the Beta distribution, and the lower and upper bounds of these Beta distributions are set to some assumed values. If we would use the method proposed in (Nakamura et al, 2022;Muslim et al, 2023), we would have reported a different outcome.…”
Section: Discussion Related To Reasonably Foreseeable Scenariosmentioning
confidence: 99%
See 3 more Smart Citations